A case study of interdisciplinary thematic learning curriculum to cultivate “4C skills” - Ye, Peiqi; Xu, Xionghu (Frontiers in Psychology, 2023)
Critical thinking, communication, collaboration, and creativity are four fundamental skills for students in the 21st century, indicating the way for nurturing talents required for future social development. Interdisciplinary thematic learning has become an important educational carrier for “4C Skills” training, with its connotation coinciding with the training requirements of “4C Skills.” Few academics, however, have looked into interdisciplinary thematic learning activities based on real-world problems. In this study, using a middle school in Xiamen, Fujian Province as an example, 32 s-year students in middle school were given several problem-solving tasks relevant to “visual disaster weather.” Based on test coding and questionnaire evaluation, class notes, course videos, student solutions, and interview texts, we examined the development of students’ 4C skills through real-world problem-based interdisciplinary thematic learning activities. This study discovered that an interdisciplinary thematic learning environment centered on real-world challenges fosters students’ creative thinking in open practice while also encouraging group communication and collaboration. Students also gain critical thinking skills through questioning and critique.